E-court: A digital disruption in law enforcement and its impact on judicial efficiency in Indonesia - Pitaloka, Diva (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The use of digital technology in thr justice system, known as E-Court, has significantly impacted law enforcement in Indonesia. This research explores E-Court as a manifestation of digital disruption, using normative legal research with a conceptual and statutory approach. Method: This research employs normative legal research with a conceptual and statutory approach to examine technological developments supporting E-Court, its benefits, and its challenges. Findings: E-Court consists of e-filing, e-payment, e-summons, and e-litigation, transforming legal case handling by improving efficiency, transparency, and accountability while reducing costs and administrative burdens. However, regulatory readiness and implementation mechanisms require further evaluation. Conclusion: E-Court has positively impacted law enforcement in Indonesia by increasing efficiency and accessibility in legal proceedings. To optimize its implementation, addressing challenges such as data security, digital infrastructure, and cultural adaptation within the legal system is essential. Novelty/Originality of this Study: This study provides a comprehensive analysis of E-Court as a digital disruption in Indonesia’s justice system, highlighting its effectiveness, challenges, and the necessity of regulatory adaptation. It contributes to developing a theoretical framework for online law enforcement systems, ensuring sustainable digital transformation in the judiciary.